Helicobacter pylori Infection and Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Heydari, Keyvan; Yousefi, Mohammad; Alizadeh-Navaei, Reza; Lotfi, Parisa; Sheydaee, Fateme; Raei, Maedeh; Vahdatinia, Alireza; Hessami, Amirhossein; Rafati, Sajjad; Moosazadeh, Mahmood; et al. (Turkish Journal of Gastroenterology, 2022)
Since numerous studies have stated that there may be a relationship between Helicobacter pylori infection and nonalcoholic fatty liver disease, and because of the high prevalence of both conditions worldwide, this study investigated the risk of non-alcoholic fatty liver disease in patients infected with H. pylori. Following a systematic review of PubMed, Scopus, Web of Science and Embase, and a search in Google Scholar using MeSH terms such as H. pylori and non-alcoholic fatty liver disease, the relevant papers up to November 2020 were reviewed. All cohort, case-control, and cross-sectional studies that examined the risk of developing non-alcoholic fatty liver disease in patients infected with H. pylori entered this study. A meta-analysis was conducted in STATA 11. This systematic review examined 22 papers with 117 117 participants (33 711 patients infected with H. pylori and 83 406 participants as control) and 20 studies were subjected to meta-analysis The results indicated a 22% to 27% increase in the risk of developing non-alcoholic fatty liver disease in patients infected with H. pylori (crude odds ratio: 1.27, 95% CI: 1.17-1.33; and adjusted odds ratio: 1.22, 95% CI: 1.09-1.35). According to the subgroup analysis, the study region, sample size, and the method of diagnosing H. pylori were the factors contributing to the high heterogeneity. The meta-analysis revealed the increased risk of developing non-alcoholic fatty liver disease in patients infected with H. pylori. This indicates that H. pylori is a serious risk factor in patients susceptible to NAFLD.